ChemInform Abstract: Shortcut Approach to Cyclopenta[b]indoles by [3 + 2] Cyclodimerization of Indole‐Derived Cyclopropanes. Issue 13 (March 2015) - Ivanova, Olga A.; Budynina, Ekaterina M.; Skvortsov, Dmitriy A.; Trushkov, Igor V.; Melnikov, Mikhail Ya.
Abstract The products show moderate cytotoxicity in vitro.